Global, regional and national burden of injuries caused by fire, heat, and hot substances from 1990 to 2021 - Shi Huang; Hui-Zhen Lin; Xin Wei (PLoS ONE, 2025)
Background Burn injuries, which are caused by fire, heat, and hot substances, are considered a chronic condition due to their long-term effects on the health of affected individuals. Moreover, burn injuries constitute a significant public health issue that cannot be overlooked within the global healthcare system. Materials and methods This study comprehensively analyzed the burden of burn injuries, focusing on variations by Socio-Demographic Index (SDI) levels and Global Burden of Disease (GBD) regions, sex-based disparities, Frontier analysis, and future trend forecasting using the Bayesian Age-Period-Cohort (BAPC) model. Results Compared to 1990, the global burden of burn injuries decreased in most regions worldwide in 2021. The majority of regions showed a negative Estimated Annual Percentage Change (EAPC), indicating a continuous decline in Age-Standardized Rate (ASR) annually. And the ASR decreased with the increasing SDI. Moreover, the forecasted trend from 2021 to 2030, indicates a continued decline with a well-fitted projection model. Conclusions Despite the observed and projected decline in global ASR of burn, the burden of burn remains a significant concern that should not be underestimated.